Optimizing Financial Well-Being Through Financial Management Behavior: A Phenomenological Study on the Sandwich Generation in Kotamobagu - Muhammad Irfan Rizki Maulana; Tri Handayani Amaliah; Ronald S. Badu (International Journal of Economics Studies, 2026)
This phenomenological study explores the financial management behaviors of the sandwich generation in Kotamobagu, North Sulawesi, Indonesia. The sandwich generation faces the unique challenge of simultaneously supporting their children and aging parents, leading to significant financial pressures. With a high population dependency ratio in Kotamobagu (43.15%), this study investigates how individuals in this generation perceive and manage their finances to achieve financial well-being. Using in-depth interviews with five individuals from diverse occupational backgrounds (trader, stall owner, service worker), the research identifies key strategies employed to navigate financial constraints. Data analysis, guided by a transcendental phenomenological approach, reveals that prioritizing spending on basic needs (food, education, healthcare) is a primary strategy. Informants also utilize simple income and expense tracking to monitor and control finances. The ability to save is a main strategy to dealing with financial uncertainty. Financial decisions are made collectively to maintain economic stability and achieve long-term financial well-being. These findings contribute to the Behavioral Finance Theory and offer practical insights for the sandwich generation, financial institutions, and policymakers in developing targeted financial literacy programs. This study provides a clearer understanding of the dynamics of financial management carried out by the sandwich generation and help them develop more effective strategies to achieve financial well-being in the midst of various challenges they face.